(untitled) (Al-Academy, 2026)
The current research dealt with (Communication and Openness of Performance Contexts in Postmodern Formation). The research included four chapters. The first chapter dealt with the methodological framework of the research represented by the research problem, which was determined by answering the following questions: - What is the concept of communication in postmodern formation? - What are the performance contexts in postmodern formation? As for the research boundaries, they were determined as follows: 1- Spatial boundaries: America. 2- Temporal boundaries: 1952-2001 As for the second chapter (the theoretical framework of the research), it dealt with the following topics: The first topic: The concept of communication and performance contexts in modern drawing. As for the second topic, it dealt with: Communication and performance contexts in postmodern formation. The third chapter was concerned with analyzing the research sample, which amounted to (3) models of postmodern formation. The fourth chapter was determined by the results and conclusions of the research. The results include: 1- Communication was based on the principle of spontaneity and continuity in addition, construction and deletion, as these continuous moments or continuous time with the artwork have a special space-time that cannot be repeated. 2- Communication was achieved through the psychological dimensions of the self in the midst of a state of alienation and disintegration, as the performances display the human body (the artist) and the animal, through a fabric of color and tactile harmonies, as the body is in a dynamic and active state continuously.